1988
DOI: 10.3109/01902148809087826
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Potentiates Asbestos-Induced Airflow Abnormalities

Abstract: It has been suggested that exposure to both asbestos and cigarette smoke can produce worse parenchymal lung disease than exposure to asbestos alone. Using a guinea pig model of asbestos administration that produces primarily airway disease and associated airflow abnormalities, we showed previously that the combination of asbestos and smoke acts synergistically to produce more marked increases in tissue collagen, fibrosis of airway walls, and early interstitial fibrosis than are seen with asbestos alone. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As there was no radiographic examination, it is not possible to know if pneumoconiosis had set in the dust-exposed workers. Lung function tests are a means of early detection of lung functional impairment even without radiographic signs of the disease (Wright et al, 1988). So frequent lung function testing in vicinity of granite rock blasting industry should be enforced and precautionary measures should be introduced in the industry studied.…”
Section: Discussionmentioning
confidence: 99%
“…As there was no radiographic examination, it is not possible to know if pneumoconiosis had set in the dust-exposed workers. Lung function tests are a means of early detection of lung functional impairment even without radiographic signs of the disease (Wright et al, 1988). So frequent lung function testing in vicinity of granite rock blasting industry should be enforced and precautionary measures should be introduced in the industry studied.…”
Section: Discussionmentioning
confidence: 99%
“…Further increases in lung cancer due to asbestos exposure are expected for the near future [11][12][13]. Combining the risk of developing lung cancer from asbestos and smoking leads to a multiplication of the risk of developing lung cancer [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac output was measured by injection of 0.25 ml cold saline into the pulmonary artery, and a thermodilution curve calculated from the aortic thermoprobe using an Edwards cardiac output computer. Pulmonary function tests were performed according to our usual protocol [3]. In brief, a 10-cm water filled catheter with multiple side holes was inserted into the esophagus to measure pleural pres sure.…”
Section: Methodsmentioning
confidence: 99%
“…We chose the intact guinea pig since it has been used successfully in this laboratory as a model of cigarette smoke-induced pulmonary emphysema [3,4], The model has shown that guinea pigs exposed to long-term cigarette smoke develop both airflow obstruction and pulmonary hypertension. Pa(x) = Mean systemic arterial pressure (cm H20); CO = cardiac output (ml/min); Cl = cardiac index (m l/m in/cm 2); HR = heart rate (beats/min): Ppa(s) = systolic pulmonary arterial pressure (cm H,0); Ppa(d) = diastolic pulmonary arterial pressure (cm H:0); Ppa(x) = mean pulmonary arterial pressure (cm H20).…”
Section: Introductionmentioning
confidence: 99%